Penerapan Prinsip 5C Pada Resiko Pembiayaan Murabahah Di BMT Istiqomah Tulungagung dan BMT Pahlawan Tulungagung - Dwi Wahyu Ningtyas (xxxx-xxxx, 2022)
This research is motivated by the development of Islamic microfinance institutions called Baitul Maal wat Tamwil. The 5C principle in BMT Istiqomah and BMT Pahlawan are used to anticipate the risk of problematic financing in the future. The problems that often occur in BMT Istiqomah and BMT Pahlawan are almost similar, namely the character of members or prospective members who are not honest. Based on this background, researchers are interested in conducting research with the title "Implementation of Character, Capital, Collateral, Capacity, and Condition Principles in the Risk of Murabaha Financing in Baitul Maal Wat Tamwil Istiqomah with Baitul Maal Wat Tamwil Pahlawan Tulungagung". This research is a field research. The number of informants from this study were 3 BMT Istiqomah employees and 5 BMT Pahlawan employees. Methods of data collection by observation, interviews, and documentation. Analysis of the data is descriptive analysis. The results of this study are the implementation of the 5C principle in Istiqomah BMT and Pahlawan BMT both using the 5C principle. But in the implementation of the principle of character is preferred in analyzing murabaha financing, the next principle is guarantee and ability. This is because BMT Istiqomah and BMT Pahlawan both do not have the ability to continue to monitor all financing that has been acc. So that the principle of character is preferred. But other principles are also considered important so that all 5C principles are still used in Istiqomah BMT and Pahlawan BMT.